Pertumbuhan Benih Ikan Nila (Oreochromis niloticus) yang Diberikan Pakan Jenis yang Berbeda secara Ad libitum - Sitepu, May Jupianto; Restu, I Wayan; Kartika, Gede Raka Angga (Current Trends in Aquatic Science; Vol 7 No 2 (2024), 2025)
This research was conducted at the Fisheries Laboratory FKP, Udayana University from March to April 2022. The fish samples tested were tilapia (Oreochromis niloticus) seeds obtained from UD. Mina Karya Jaya, Karangasem, Bali. The feed in this study was pellets, Hong Kong caterpillars, earthworms. The method used in this study was a completely randomized design (CRD) method with 3 treatments and 3 repetitions, namely A, B, C. Research data were analyzed using Analysis of Variance (ANOVA) using SPSS. The results showed that the highest absolute length growth of tilapia was in treatment A of 5.05 cm. Results of the ANOVA analysis showed that the provision of different types of feed was not significantly different on the length growth of tilapia. The highest growth in absolute weight of tilapia was in treatment A 21.93 g. Results of ANOVA analysis with duncan's follow-up test showed that treatment A was significantly different from treatments B and C. The lowest feed conversion ratio for tilapia was found in treatment A 2.02. Results of the ANOVA analysis showed that there was no significant difference in the FCR of tilapia. Highest survival rate was found in treatment B 80%. Results of the ANOVA analysis with Duncan's follow-up test showed that treatment C was not significantly different from treatments A and B, but treatment A and treatment B obtained significantly different results. Parameters obtained were pH in the range of 6.03-7.97, DO in the range of 6.34 – 7.97 mg/L and temperature in the range of 27.1-28.1?.